MANAGING OLDER WORKER’S PERFORMANCE: A CHALLENGE FOR POLISH ORGANIZATIONS - Ulrych, Wojciech; Syper-Jędrzejak, Marzena (Journal of Positive Management, 2018)
Purpose: This paper outlines the present and prospective conditions and practices of managing older employees in Poland from a performance management (PM) viewpoint. It sets out a general framework in this regard. There are very few good examples of how to manage this specific kind of workforce from a system-oriented approach. This is why a comprehensive approach is underlined in this paper. Methodology: A holistic understanding of managing employee performance is driven by a three-stage cycle consisting of planning, supporting and assessing performance. It should be tailored to older worker’s needs and be derived from age management assumptions. Findings: This paper points out that older workers are broadly found to be an underestimated workforce with a set of valuable competencies that can still keep up to date with the modern economy. However, to get more out of the workforce it is a must to join a system-based PM framework with more sophisticated managerial competencies, based on a specific mix of soft and hard skills. There are very few complex findings in the Polish literature in this regard. Implications for practice: Poland is now at the edge of introducing a new age management approach with employee performance management practices at its core. In the next 25 years it is a must for Polish companies to teach themselves how to manage the older workforce. Managing the staff in question is not just about meeting the age management guidelines, but translating the concept ideas into a real functioning performance-oriented system, to be put into practice between subordinates and their superiors at the lowest level of the organizational hierarchy. Originality/value: This paper includes proposals and suggestions for practices to be used in managing the performance of older workers, as well as indicating links between employee performance management and different HRM practices. This system-based PM approach is a must to move forward in the twenty first century.